If you have questions, feel free to ask
Answer:
4m and ms are peanut
Step-by-step explanation:
9+2=11 and theres 15 total so 15-11= 4
Answer:
= 9y^4 -6y^3 -17y^2 -18y -10
Step-by-step explanation:
(3y^2 + 2y + 2) x (3y^2 – 4y – 5)
9y^4 - 12y^3 - 15y^2 + 6y^3 -8y^2 -10y +6y^2 -8y -10
= 9y^4 -6y^3 -17y^2 -18y -10
Step-by-step explanation:
1.
![\tan \beta = \frac{1}{ \cot \beta } = - \frac{3}{2 \sqrt{10} } = - \frac{3 \sqrt{10} }{20}](https://tex.z-dn.net/?f=%20%5Ctan%20%5Cbeta%20%20%3D%20%20%5Cfrac%7B1%7D%7B%20%5Ccot%20%5Cbeta%20%7D%20%20%3D%20%20-%20%20%5Cfrac%7B3%7D%7B2%20%5Csqrt%7B10%7D%20%7D%20%20%3D%20%20-%20%20%5Cfrac%7B3%20%5Csqrt%7B10%7D%20%7D%7B20%7D%20)
![\csc \beta \tan \beta = \frac{1}{ \cos \beta } = \sec \beta](https://tex.z-dn.net/?f=%20%5Ccsc%20%5Cbeta%20%20%5Ctan%20%5Cbeta%20%20%3D%20%20%5Cfrac%7B1%7D%7B%20%5Ccos%20%5Cbeta%20%20%7D%20%20%3D%20%20%5Csec%20%5Cbeta%20)
Therefore,
![\sec \beta = ( \frac{7}{3} )( - \frac{3 \sqrt{10} }{20} ) = - \frac{7 \sqrt{10} }{20}](https://tex.z-dn.net/?f=%20%5Csec%20%5Cbeta%20%20%3D%20%28%20%5Cfrac%7B7%7D%7B3%7D%20%29%28%20-%20%20%5Cfrac%7B3%20%5Csqrt%7B10%7D%20%7D%7B20%7D%20%29%20%3D%20%20-%20%20%5Cfrac%7B7%20%5Csqrt%7B10%7D%20%7D%7B20%7D%20)
2.
![\csc y = \frac{1}{ \sin y} = - \frac{ \sqrt{6} }{2}](https://tex.z-dn.net/?f=%20%5Ccsc%20y%20%3D%20%20%5Cfrac%7B1%7D%7B%20%5Csin%20y%7D%20%20%3D%20%20-%20%20%5Cfrac%7B%20%5Csqrt%7B6%7D%20%7D%7B2%7D%20)
![= > \sin y = - \frac{ \sqrt{6} }{3}](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20%20%5Csin%20y%20%3D%20%20-%20%20%5Cfrac%7B%20%5Csqrt%7B6%7D%20%7D%7B3%7D%20)
Use the identity
![\cos y = \sqrt{1 - \sin ^{2} y} \: \: \: \: \: \: \: \: \: \: \: \\ = \sqrt{1 - {( - \frac{ \sqrt{6} }{3}) }^{2} } = - \frac{ \sqrt{3} }{3}](https://tex.z-dn.net/?f=%20%5Ccos%20y%20%3D%20%20%20%5Csqrt%7B1%20-%20%20%5Csin%20%5E%7B2%7D%20y%7D%20%20%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%5C%20%3D%20%20%5Csqrt%7B1%20-%20%20%7B%28%20-%20%20%5Cfrac%7B%20%5Csqrt%7B6%7D%20%7D%7B3%7D%29%20%7D%5E%7B2%7D%20%7D%20%20%3D%20%20-%20%20%5Cfrac%7B%20%5Csqrt%7B3%7D%20%7D%7B3%7D%20)
We chose the negative value of the cosine because of the condition where cot y > 0. Otherwise, choosing the positive root will yield a negative cotangent value. Now that we know the sine and cosine of y, we can now solve for the tangent:
![\tan \beta = \frac{ \sin y}{ \cos y} =( - \frac{ \sqrt{6} }{3} )( - \frac{3}{ \sqrt{3} } ) = \sqrt{2}](https://tex.z-dn.net/?f=%5Ctan%20%5Cbeta%20%20%3D%20%20%5Cfrac%7B%20%5Csin%20y%7D%7B%20%5Ccos%20y%7D%20%3D%28%20-%20%20%5Cfrac%7B%20%5Csqrt%7B6%7D%20%7D%7B3%7D%20%29%28%20-%20%20%5Cfrac%7B3%7D%7B%20%5Csqrt%7B3%7D%20%7D%20%29%20%3D%20%20%5Csqrt%7B2%7D%20)
3. Recall that sec x = 1/cos x, therefore cos x = 5/6. Solving for sin x,
![\sin x = \sqrt{1 - \cos ^{2} x} = \sqrt{ \frac{11}{6} }](https://tex.z-dn.net/?f=%20%5Csin%20x%20%3D%20%20%20%5Csqrt%7B1%20-%20%20%5Ccos%20%5E%7B2%7D%20x%7D%20%3D%20%20%5Csqrt%7B%20%5Cfrac%7B11%7D%7B6%7D%20%7D%20)
Solving for tan x:
![\tan x = \frac{ \sin x}{ \cos x} = (\frac{ \sqrt{11} }{ \sqrt{6} } )( \frac{6}{5} ) = \frac{ \sqrt{66} }{5}](https://tex.z-dn.net/?f=%20%5Ctan%20x%20%3D%20%20%5Cfrac%7B%20%5Csin%20x%7D%7B%20%5Ccos%20x%7D%20%20%3D%20%20%28%5Cfrac%7B%20%5Csqrt%7B11%7D%20%7D%7B%20%5Csqrt%7B6%7D%20%7D%20%29%28%20%5Cfrac%7B6%7D%7B5%7D%20%29%20%3D%20%20%5Cfrac%7B%20%5Csqrt%7B66%7D%20%7D%7B5%7D%20)
Answer:
0.635
Step-by-step explanation:
1/4 x 2.54 = 0.635
:)